Research on Evaluation Factors of Intelligent Level of Dam Safety Monitoring System. Issue 1 (March 2020) - Lu, Qiling; Wang, Xue; Yu, Keping
Abstract: With the continuous improvement of intelligence level, intelligent evaluation of a safety monitoring system has become the key to system evaluation. In order to improve the pertinence of evaluation, according to the application environment and demand of dam safety monitoring, this paper makes an in-depth study on the evaluation factors of the intelligent level of dam safety monitoring system from the system occurrence environment, system composition, network communications, system function and performance, channel protection and power control, remote maintenance, system parameters, running log, statistical analysis, rule discovery, hidden trouble diagnosis, maintenance advice, method and expert recommendation algorithm, intelligent query and human-computer interaction, etc., providing a beneficial reference for the evaluation of improving the intelligent level of dam safety monitoring system.